PREBIOTICS AS A «FUNCTIONAL» COMPONENT OF CHILD NUTRITION - S. G. Makarova (Вопросы современной педиатрии)
This review represents a modern view to the intestinal microbiocenosis and possibilities of influence on it with the means of prebiotic food components. Status of intestinal microbiota is one of the main factors of children health. As it was shown in the recent studies, certain constancy of microbiota of every individual in many respects is determined genetically. Intestinal microflora directly influence on the formation of the child immune system, provide protection from pathogens and participates in all types of metabolism. In its turn the intestinal microbiocenosis itself depends on the status of the macroorganism and exogenous factors, with nutrition being the most significant of them. As a matter of fact, there is a combined evolution of nutrition, intestinal microbiocenosis and intestinal mucous membrane with associated to it lymphoid tissue. Supplementation of nutritive components, contributing to vegetation of the «useful» microflora, with food is an effective mechanism of «dietary manipulation» of intestinal biocenosis. Biological effects of prebiotics are discussed in detail. Oligosaccharides of the breast milk have a number of biological effects, which exceed the limits of only prebiotic action. However including of prebiotic components with proved effects into children milk formulas and porridges adds these products prophylactic and therapeutic-prophylactic characteristics.